Traffic Management Using Intelligent Transportation System Based On Vehicular Ad Hoc Networks - Kiros, Fisseha (ASTU, 2022)
As The World's Cities Grow In Number, The Total Number Of Mobility Of Human Population From And To In The Cities Also Increases, In Addition There Has Also Been An Increase In The Number Of Driving Vehicles On The Public Roads. The Outcome Is, Traffic Congestion, Vehicular Accidents, And Environmental Pollution Are On The Rise. Car Accidents Are Still A Major Concern, Despite The Fact That Various Systems Have Been Developed Using Sophisticated Technology. However, Behind This Problem There Has Been Created A Promising VANET Technology That Could Solve The Vehicular Accident In The Transportation Sector. The Principles Of Mobile Ad Hoc Networks (Manets) The Spontaneous Establishment Of A Wireless Network Of Mobile Devices Are Applied To The Domain Of Automobiles To Produce Vehicular Ad Hoc Networks (Vanets). Therefore, Vanets Were Created From Manets By Driving Their Principles. Vanets (Vehicular Ad Hoc Networks) Are A Type Of Wireless Network That Are Used To Communicate Between Automobiles And Roadside Equipment Using An Open Source Wireless Protocol Wireless Access Vehicular In Environments (WAVE) IEE802.11p Based Designed By FCC For The Purpose Of Short To Medium Range Communication Technology That Operates In The 5.9 Ghz Band Of Frequency With Bandwidth Of 75mhz For The Use Of Public Transportation System. Vanets Are Primarily Used To Provide Safety And Comfort To Drivers And Passengers In Vehicle Situations. Therefore, It Is Important To Develop Common Improved System For Traffic Management System. Starting Decades Ago There Has Also Been Tried To Design Globally Traffic Management System, However Designing Of An Algorithm For An Effective Vehicular Management System Remains Still A Major Challenge That Must Be Overcome And Delays And Speed Controlling Are The Gaps That Are Identified To Be Solved In Our Thesis. The Aim Of This Thesis Is To Design Communication Of Traffic Transportation Intelligent System Using Vanets To Decrease Vehicular Accident To Save Human Life In Public Transport By Solving The Delays And Controlling Speed Of Vehicles. This Thesis Solved The Gap Using Euclidean Distance Algorithm By Creating Communications Among Vehicles And Infrastructures On The Road. Simulation Results Demonstrate That The Suggested Traffic Control System Is Feasible And Increased The Waiting Time In Communication Coverage Area By 100% Which Is Solved The Time Delay And The Collision Of The Vehicles Also Being Managed By Controlling The Speed Of Each Vehicle.
Keywords: Vehicular Ad Hoc Networks, Road Side Unit, On Board Unit, Dedicated Short Range Communication, Wireless Access In Vehicular Environment